Sculpture in the Philippines from Anito to Assemblage and other essays - Guillermo, Alice; Jose, Regalado Trota; Pilar, Santiago A.; Javelosa, Jeannie E.; Roa, Lourdes Ruth R.; Alvina, Corazon S. (Metropolitan Museum of Manila, 1991)
Complements the exhibition "Iskultura" on the occasion of the birth centenary of Guillermo Tolentino, the first Philippine National Artist for Sculpture.